Legal regime of the Churches, Faiths and Religious communities in Spain - Ruano Espina, Lourdes (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
In Spanish law we do not find a univocal concept of religious denomination, but the juridical norms that refer to the collective subjects of the right of religious freedom, often use a highly varied terminology, referring, indistinctly, to the Churches, Faiths and Religious communities. The Spanish constitutional text, while proclaiming the non-denominational state, recognizes religious faiths as having full rights to religious freedom, under conditions of equality. However, the diverse legal nature, organizational structure and sociological implementation of the different religious denominations has, in practice, meant that the legislation applicable to each of them is also different, without thereby compromising equality and nondiscrimination. This paper analyzes the specific legal regime of different types of churches, faiths and religious communities in Spain, which is different from that of associative entities, which are subject to common law.